A novel microwave absorption material of Ni doped cryptomelane type manganese oxides. Issue 4 (May 2015) - Guan, Hongtao; Wang, Yan; Dong, Chengjun; Chen, Gang; Xiao, Xuechun; Wang, Yude
Abstract: Cryptomelane type manganese oxide α-MnO2 and Ni doped KMn8 O16 nanostructures were synthesized by water-bathing methods at 80 °C for 24 h using NiSO4 ·H2 O as the dopant sources. The structures, morphologies and physical properties were investigated by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The results show that the products are Ni doped KMn8 O16 nanorods after the introduction of NiSO4 ·H2 O during the reaction process. The electromagnetic characteristics and microwave absorption properties of the materials were carried out with a vector network analyzer (VNA) and the transmission line (TML) theory. The dielectric loss and microwave absorption properties of the cryptomelane materials are improved after Ni doping. The thickness dependent reflection loss shows that the peak frequency and effective absorption bandwidth all decrease with the increasing material thickness. With the increase of Ni doping concentration, the peak frequency shifts to higher frequency bands and the effective absorption bandwidth increases. The electromagnetic performance of cryptomelane can be attributed to its unique tunnel structures and the improvement of Ni doping can be due to the enhanced electromagnetic polarization.